2016
DOI: 10.12681/mms.1712
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and trophic diversity in molluscan assemblages from the Bay of Tunis (southern Mediterranean Sea)

Abstract: Soft bottom molluscan assemblages from the Bay of Tunis have been studied in order to analyse their seasonality and trophic diversity in relation to environmental variables. A total of 147 species of molluscs was identified, with gastropods displaying the highest species richness and bivalves the highest abundances, and including five non-indigenous species such as the dominant ectoparasite Polycerella emertoni. Carnivorous and scavenger gastropods were among the most frequent species, reflecting a diverse ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…The dominant species found in our study are characteristic of areas of debris accumulation, associated with the presence of Zostera, Halophila, Cymodocea and Posidonia seagrass meadows. The molluscan fauna studied here is very similar to that of the shallow seagrass beds of Tunis Bay described by [16]. These authors reported a dominance of Varicorbula gibba, accompanied by most of the predominant species found in the current tidal streams of the Gulf of Gabès; in Tunis Bay, the temporal pattern of abundance is almost identical to that observed in the Gulf of Gabès, with maximum abundances in winter (January) becoming minimal in autumn (November).…”
Section: Comparison With Other Mediterranean Malacofauna Assemblagessupporting
confidence: 83%
See 2 more Smart Citations
“…The dominant species found in our study are characteristic of areas of debris accumulation, associated with the presence of Zostera, Halophila, Cymodocea and Posidonia seagrass meadows. The molluscan fauna studied here is very similar to that of the shallow seagrass beds of Tunis Bay described by [16]. These authors reported a dominance of Varicorbula gibba, accompanied by most of the predominant species found in the current tidal streams of the Gulf of Gabès; in Tunis Bay, the temporal pattern of abundance is almost identical to that observed in the Gulf of Gabès, with maximum abundances in winter (January) becoming minimal in autumn (November).…”
Section: Comparison With Other Mediterranean Malacofauna Assemblagessupporting
confidence: 83%
“…Despite recent studies mainly in Tunisia waters [3,5,11,14,16,17] (see Figure 8), there is still relatively little published research on molluscs from the coastal waters of southern Tunisia, including the Gulf of Gabès [6,7,[28][29][30][31][32][33][34][35][36][37].…”
Section: Main Characteristics Of the Malacofauna Of The Tidal Channel...mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional (trophic) diversity of the molluscan assemblages at each habitat was analysed through the Index of Trophic Diversity (ITD) (Help et al, 1998), which ranges from 0 to 1 (high and low trophic diversity, respectively), and is calculated according to the following equation: individuals. According to the modified version applied to molluscs (Antit et al, 2016), ITD was calculated as 1-ITD to have the highest trophic diversity with the greatest weight. Differences in the structure of mollusc assemblages both in Habitats and Sites (two fixed and orthogonal factors) were evaluated through a permutational analysis of variance (PERMANOVA, Anderson, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Trophic diversity (TrD) was calculated for each sample following Antit et al (2016): trophic categories were used instead of species for calculating the Shannon‐Wiener diversity index (Data S1), which is similar to the more intuitive inverse form of the Index of Trophic Diversity (ITD, Heip et al, 1998). Six trophic categories were used for estimating trophic diversity, based on Rueda et al (2009): (1) carnivores/scavengers, (2) herbivores; (3) micrograzers; (4) ectoparasites; (5) suspension feeders; and (6) omnivores.…”
Section: Methodsmentioning
confidence: 99%